O casamento como manifestação de uma cultura: o caso de Nova Palmira - Bettega, Maria Lúcia (My University, 2014)
This study has as objective to analyze through a rite of passage the cultural values present in a rural community. When narrating their memories, the inhabitants of this community bring to discussion the experiences lived in the wedding rite and the meanings that they represented in their lives. The richness of this qualitative study sustains itself in the possibility of deeply knowing these experiences, analyzing the cultural aspects which they organize themselves in and what they represent for their maintenance. The research uses ethnography as methodological basis and the semi-structured narrative interview as the data gathering technique. The sample is intentional consisting of thirty interviewees from three distinct generations. The subject selection criteria to take part in the research were: marital status, residence at the place of research, age and gender. Based on these variables, three interviewee groups were created divided by distinct ages in order to distinguish the generations. The theoretical referential used enabled the analysis of this community`s culture through Van Gennep, Turner, Segalen and DaMatta works, and to identify the rite of passage stages and the values inserted in this rite at the community. This way the study around these narratives contributed to show that this rite maintains itself in the community as part of the culture and social values that constitute its culutural identity. The study even demonstrates that the rites are products of social forces and that they maintain themselves alive despite the speed at which the society develops.
Este estudo tem como objetivo analisar, através de um ritual de passagem, os valores culturais presentes em uma comunidade rural. Ao narrar suas lembranças sobre o rito de passagem, os moradores dessa comunidade trazem para a discussão as experiências vividas no rito do casamento e os significados que elas representaram em suas vidas. A riqueza desse estudo qualitativo sustenta-se na possibilidade de entrar nessas experiências, analisar em que aspectos da cultura elas se estruturam e o que representam para sua manutenção. A pesquisa usa a etnografia como base metodológica e a entrevista narrativa semi-estruturada como técnica de coleta de dados. A amostra é intencional, composta por trinta entrevistados, de três diferentes gerações. Os critérios de seleção dos sujeitos para participarem da pesquisa foram: estado civil, residência no local em estudo, idade e sexo. A partir dessas variáveis, foram criados três grupos de entrevistados, divididos por idades distintas, a fim de caracterizar as gerações. O referencial teórico utilizado permitiu analisar a cultura dessa comunidade, através das obras de Van Gennep, Turner, Segalen e DaMatta, e identificar as etapas de um rito de passagem e dos valores inseridos nesse rito na comunidade. Desse modo, o estudo acerca dessas narrativas contribuiu para mostrar que esse rito se mantém na comunidade como parte da cultura e dos valores sociais que constituem sua identidade cultural. O estudo demonstra ainda que os ritos são produtos das forças sociais e que se mantêm vivos apesar da velocidade com que a sociedade se desenvolve.
Keywords: Ciências Sociais Aplicadas; Rituais de passagem; Cultura; Nova Palmira (Caxias do Sul, RS); Comunidades rurais; Identidade cultural; Valores culturais; Rite of passage; Cultural values; Cultural identity; Rural community